Semiconducting Polymer Nanoparticles with Intramolecular Motion-Induced Photothermy for Tumor Phototheranostics and Tooth Root Canal Therapy - Duan, Xingchen (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.